Honduras : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report analyzes corporate financial reporting and auditing practices in Honduras in support of the Government's efforts to : (a) improve the business environment and make it more attractive for domestic and foreign direct investment; (b) enhance financial transparency and governance in the corporate sector; and (c) foster economic integration within the Latin America and Caribbean Region (LCR). For the purpose of this study, relevant benchmarks have been used, including the International Financial Reporting Standards (IFRS) and the International Standards on Auditing (ISA). The report also draws on international experience and good practice in those fields, particularly in LCR. Accounting and auditing (A&A) standards and practices in Honduras have been improving; however, continued efforts to align these with international ones are still needed. The review focuses on the strengths and weaknesses of the accounting and auditing environment in the corporate sector (which includes private companies and state-owned enterprises) and how they influence the quality of corporate financial reporting.